A Retrospective study on Non Fatal Motor Vehicle Accident cases in the Emergency Department, Saveetha Medical College, Chennai (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim & Objectives: To retrospectively study non fatal RTAs in the emergency department of SMCH withhelp of AR registers while studying various factors involving like pattern, site and time of injuries and ageof the person involved.Materials and Methodology: Data was collected for complete one year and all the cases in the year wereincluded in the study, which thus constitute sample for the study. The retrospective study group consisted ofall the RTA victims reporting to Emergency Department of SMCH in the study period from 1st January 2018to 31st December 2018. These collected data were compiled with help of Excel.Results: In this study a total of 911 cases were included who were admitted in the emergency departmentof SMCH. Males were the most commonly involved. Around 95% of the cases involved 2 wheelers. 65%of the accidents took place in the 6pm to 9pm range. Commonly involved age group is 18-30. 20% showedhead injuries but the majority had injured their limbs.Conclusion: This suggests that there has to be more awareness created amongst the youth populationencouraging them to wear helmets and seat belts. More advancement is required in the field of automotivesafety. Road safety must be embedded in the children’s curriculum from lower grade itself. More involvementof Traffic police, NGOs and other public awareness groups are required to enforce this.
Keywords: Accidents, Awareness, Non-fatal injury, Trauma